2023
DOI: 10.3233/nre-230014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anodal tDCS on electroencephalography correlates of cognitive control in mild-to-moderate traumatic brain injury

Nickolas Mertens,
James Cavanagh,
Emma Brandt
et al.

Abstract: BACKGROUND: Transcranial direct current stimulation (tDCS) may provide a potential therapy for cognitive deficits caused by traumatic brain injury (TBI), yet its efficacy and mechanisms of action are still uncertain. OBJECTIVE: We hypothesized that anodal tDCS over the left dorsolateral prefrontal cortex (DLPFC) would boost the influence of a cognitive training regimen in a mild-to-moderate TBI (mmTBI) sample. Cognitive enhancement was measured by examining event-related potentials (ERPs) during cognitive cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Although it is not our intention here to fully review the vast literature on neural responses to TDCS, we note that even limiting ourselves to studies examining time-domain electromagnetic activity (ERPs and ERFs), examples can be found in line with our findings, contrary to our findings, and with null results from TDCS. Supporting the neural gain hypothesis, a fairly large number of studies have now demonstrated increases in the P300 potential after anodal stimulation, corresponding to behavioral improvements in cognitive control, target detection, and related measures (reviewed by Mendes et al, 2022 ; Liu et al, 2023 ; Mertens et al, 2023 ; Zhou et al, 2023 ). Some studies have also reported decreased N2 potentials after cathodal stimulation in a go/nogo paradigm (Friedrich and Beste, 2018 ), and increased auditory N2 (Hanenberg et al, 2019 ) and mismatch negativity (MMN) responses (Impey and Knott, 2015 ) after anodal stimulation.…”
Section: Discussionmentioning
confidence: 96%
“…Although it is not our intention here to fully review the vast literature on neural responses to TDCS, we note that even limiting ourselves to studies examining time-domain electromagnetic activity (ERPs and ERFs), examples can be found in line with our findings, contrary to our findings, and with null results from TDCS. Supporting the neural gain hypothesis, a fairly large number of studies have now demonstrated increases in the P300 potential after anodal stimulation, corresponding to behavioral improvements in cognitive control, target detection, and related measures (reviewed by Mendes et al, 2022 ; Liu et al, 2023 ; Mertens et al, 2023 ; Zhou et al, 2023 ). Some studies have also reported decreased N2 potentials after cathodal stimulation in a go/nogo paradigm (Friedrich and Beste, 2018 ), and increased auditory N2 (Hanenberg et al, 2019 ) and mismatch negativity (MMN) responses (Impey and Knott, 2015 ) after anodal stimulation.…”
Section: Discussionmentioning
confidence: 96%
“…tDCS has been established as an effective therapeutic approach for TBI, with research indicating its absence of side effects [ 34 , 35 ]. In terms of its therapeutic mechanism, specifically, anodal current exerts an excitatory effect on neuronal activity, while cathodal tDCS exhibits inhibitory properties [ 36 ]. A study has highlighted the ability of anodal tDCS to enhance reaction times in working memory tasks for patients with mild to moderate brain injuries, providing crucial therapeutic insights for their recovery [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, anodal tDCS has demonstrated the potential to promote cerebrovascular reactivity in cerebral parenchymal arterioles, regulating average cerebral blood flow and tissue oxygenation in traumatized mice, thus potentially contributing to the improvement of neurological function [ 15 , 38 ]. Despite being considered an effective therapeutic modality for TBI, the molecular mechanisms governing the effects of tDCS are still not fully understood [ 36 ]. Hence, in this research, we proceeded to examine the impact of tDCS on vascular regeneration and angiogenesis in a rat model of TBI.…”
Section: Discussionmentioning
confidence: 99%